THE AESTHETICS OF RUINS: FAILURE, DECAY, PLANNING AND POVERTY - Sarmento, João (Finisterra, 2019)
Ruins take many shapes and result from numerous and diverse human and non-human interactions. Acknowledging their place and arrangements, considering their spatial orderings, evaluating hierarchies, patterns and significations, and unravelling their ‘performance’, role, effect and marked absences, is key to a critical and significant engagement with the politics, grammars and productive power of materials that are in place. Ruins are material sites that animate new possibilities of living: they should be perceived as dynamic and relational, as interstitial, as sites of plurality, plasticity, dismantling and destabilizing the power of endless self-invention. Schönle’s (2006: 652) argument that ‘we cannot leave ruins alone and let them simply exist in their mute materiality’ guides the following four examples. While ruins pose challenges to planners and to politicians, constituting threats and opportunities, they speak to us of decadence, failure, loss, beauty, change and pleasure.